FEASIBILITY TEST FOR LEARNING INNOVATION ON ARABIC TEACHING IN INDONESIAN HIGHER EDUCATION: STUDY ON TARKIB MUKATSTSAF IBTIDA’I - Fauzan, Moh; Thoriquttyas, Titis; Dariyadi, Moch Wahib (STIQ Amuntai, 2020)
The emergency of the new era, namely industrial era 4.0, is a challenge and opportunity in all aspects of life, including education’s field. Along with the emergence of challenges and opportunities, there need to be new breakthroughs in innovation for developing the learning courses, namely Tarkib Mukatstsaf Ibtida'i. This course is a compulsory subject for students of the Department of Arabic Letter, Faculty of Letters, State University of Malang (JSA, FS, UM). This study was designed to test the feasibility of android-based Arabic language learning innovations in tertiary institutions. The subjects of this study were students of JSA, FS, UM as respondents, lecturers of educational technology departments, UM as media experts and lecturers of Arabic letter, UM as material experts. The results of the validation test of Tarkib Mukatstsaf Ibtida'i's teaching materials product conducted by material experts are 95%, which means these teaching materials are very valid and very feasible to be used in learning. The results of validation from media experts, the value of this product is 95.38% means that this teaching material is very valid and very feasible to be used in learning. While the average results of the assessment from correspondents amounted to 82.35%, meaning that these teaching material products are very valid and sifted worthy to be used in learning Keyword: Tarkib Mukatstsaf Ibtida'i, feasibility test